INTERVENTIONS IN THE FACE OF PRESSURE INJURY PREVENTION IN PATIENTS HOSPITALIZED IN INTENSIVE CARE UNITS (ICU) - Maria Coutinho Dias, Grazielle; Maria da Silva, Maysa; Fabiola Acíoly da Silva, Maysa; Grazielly dos Santos Lima, Leticia; de Melo , Dayana; do Vale Coutinho, Vanice; Beatriz Carolina dos Santos, Julia; Eduarda dos Santos Teixeira, Maria; Ferreira dos Santos, Amanda; Kurt Reis de Morais Rezende Dante Machado, Brenna (Health and Society, 2023)
Identify and understand nursing interventions in the face of pressure injury prevention in patients hospitalized in Intensive Care Units (ICU). Identifying extrinsic/intrinsic factors, scientific knowledge about risk factors, classification, diagnosis and nursing care in the face of pressure injury prevention in patients hospitalized in the Intensive Care Unit (ICU). Identify the nursing interventions in the face of pressure injury prevention in hospitalized patients. Descriptive study of the integrative review type of the literature. Research source: LILACS, BENF, MEDLINE. After applying the inclusion and exclusion criteria, the study sample consisted of 18 articles, filtered between the years of 2017 to 2022, where these studies address the intervention of nursing in the prevention of pressure injury in patients hospitalized in the Intensive Care Unit (ICU). This article showed that nursing interventions are of fundamental importance, and it should be emphasized the constant need to seek technical-scientific knowledge about pressure injury and consequent preparation and execution of treatment plan in order to contribute to the prevention of the emergence of LPP in hospitalized patients in ICU, thus promoting shorter hospital stay and better quality of life in the face of reduced complications resulting from the emergence of a LPP.